Pengaruh Harga dan Kualitas Produk Terhadap Keputusan Pembelian Produk Skincare Skintific - Aditya Dwi Hardianti; Agatha Faza; Fatimatul Zahra Lucky Setyowati; Ikfina Amaliadina; Nurul Hikmah; Puja Endah Suwardani Putri; Trisetyana Adiy (Universitas Muhammadiyah Surakarta, 2025)
This study aims to analyze the effect of price and product quality on purchasing decisions for Skintific skincare products. In an era of increasingly tight competition in the beauty industry, a deep understanding of the factors that influence consumer purchasing decisions is very important. The method used in this study was a survey involving 100 respondents who were active consumers of Skintific products. The data obtained were analyzed using regression techniques to identify the relationship between price variables, product quality, and purchasing decisions. The results of the analysis show that both price and product quality have a positive and significant influence on purchasing decisions. This study provides important insights for companies in formulating effective marketing strategies to increase competitiveness in the increasingly competitive skincare market. By understanding these factors, companies can better design products and marketing campaigns that meet consumer expectations.